Thaumarchaeal and sterol data at monthly to quarterly resolution from Santa Barbara Basin sediment via mass spectrometry imaging - Alfken, Susanne; Wörmer, Lars; Lipp, Julius S; Napier, Tiffany J; Elvert, Marcus; Wendt, Jenny; Schimmelmann, Arndt; Hinrichs, Kai-Uwe (PANGAEA, 2021)
Molecular biomarker data from isoprenoidal tetraethers from planktonic archaea and C29 sterols measured with the extraction-free approach of MALDI FT-ICR-MS in annually varved sediments from the Santa Barbara Basin deposited from AD 1900 - 2009.
Keywords: Mass spectrometry imaging; Santa Barbara Basin box core SPR0901-05BC; varves